The impact of B2O3/Al2O3 substitution on physical properties and γ-ray shielding competence of aluminum-borate glasses: comparative study - Abouhaswa, A. S.; Abdelghany, A. M.; Alfryyan, Nada; Alsaif, Norah A. M.; Rammah, Y. S.; Nabil, Islam M. (Journal of materials science. Materials in electronics, 2024)
This work investigates the impact of B 2 O 3 /Al 2 O 3 substitution on the physical properties and γ-ray shielding parameters in the γ-energy range of 0.015: 15 MeV of the aluminum-borate glasses with the composition: (75-X)B 2 O 3 + 10ZnO + 10CdO + 5Na 2 O + XAl 2 O 3 where X = 5 (BNCZAl-5)–20 (BNCZAl-20)% mol (with step of 5%). Samples were fabricated using the well-known melt quenching technique. The density (ρ) increased gradually from 3.492 to 3.901 g/cm 3 and molar volume (V m ) decreased from 22.311 to 21.216 cm 3 /mol as the Al 2 O 3 content increased from 5 to 20 mol%. The oxygen molar volume (OMV) increased from 9.107 to 9.868 cm 3 /mol, while the oxygen packing density (OPD) values decreased from 109.810 to 101.341 g.atom/l. Linear-attenuation coefficient (μ) followed the order: BNCZAl-5 < BNCZAl-10 < BNCZAl-15 < BNCZAl-20. The sample that coded as BNCZAL-20 (highest content of Al 2 O 3 ) possessed the lowest half-value (HVL) and tenth-value (TVL) layers among all studied samples. Within the investigated energy range of Zef Z ef within the range: from 27.324 to 10.783, 26.820 to 10.957, 26.351 to 11.128, and 25.915 to 11.296 for the prepared samples BNCZAl-5, BNCZAl-10, BNCZAl-15, and BNCZAl-20 glasses, respectively. The obtained results confirmed that the suggested glasses can be used as alternative materials for radiation shielding applications.